USE OF THIAMETHOXAM, ASSOCIATED WITH INSECT POPULATIONS IN PAPAYA (Carica Papaya Linnaeus) CULTIVATION - Megchún-García, Juan Valente; Chávez, María del Refugio Castañeda; Rodríguez-Lagunes, Daniel Arturo; Adame-García, Jacel; Murguía-González, Joaquín; Lango- Reynoso, Fabiola; Leyva-Ovalle, Otto Raúl (International Journal of Research -GRANTHAALAYAH, 2018)
Papaya crops areas present phytosanitary problems since neonicotinoid pesticides are currently applied without efficient control methods. It is necessary to study insects behavior associated with this type of crop in response to the use of the neonicotinoid thiamethoxam. In order to know the efficiency of this insecticide, different doses were evaluated for the control of the type of insects referred to below. The study area was the locality of Mata Tambor in Cotaxtla, Veracruz, Mexico. Where a plot of papaya "Maradol" of 2,778 plants ha-1 was established, applying different doses of thiamethoxam during the process: T1) 0 kg/ha; T2) 0.3 kg/ha; T3) 0.4 kg/ha; and T4) 0.6 kg/ha. The variables were: insect population, gross mortality rate and the identification of pests that cause damage to the crop. No significant statistical differences were found in insect populations when applying those different doses. The mortality rate 16 days after applying thiamethoxam was higher in T3 at a dose of 0.4 kg/ha, this response is attributed to the fact that the insecticide achieved a residual effect on the culture. The use of T2 with a dose of 0.3 kg/ha in the crop became effective in pest control, generating a gross mortality rate of 241 individuals. Papaya cultivation can be associated with pests such as Bemisia tabaci, Myzus persicae, Frankliniella occidentalis and Toxotrypana curvicuada, which are the main vectors of virus in the culture.